2019
DOI: 10.1161/jaha.118.011139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus and Chronic Kidney Disease on Cardiovascular Outcomes and Platelet P2Y 12 Receptor Antagonist Effects in Patients With Acute Coronary Syndromes: Insights From the PLATO Trial

Abstract: Background There are limited data on how the combination of diabetes mellitus ( DM ) and chronic kidney disease ( CKD ) affects cardiovascular outcomes as well as response to different P2Y 12 receptor antagonists, which represented the aim of the present investigation. Methods and Results In this post hoc analysis of the PLATO (Platelet Inhibition and Patient Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
2
23
0
2
Order By: Relevance
“…These benefits were not associated with increased bleeding risk, indicating that ticagrelor is both effective and safe. A similar pattern was observed in the subgroup with diabetes, with a HR of 0.88 (95% CI 0.76 to 1.03) for primary composite end point (myocardial infarction, stroke or cardiovascular death) with no clear increase in bleeding risk [41].…”
Section: Secondary Preventionsupporting
confidence: 61%
“…These benefits were not associated with increased bleeding risk, indicating that ticagrelor is both effective and safe. A similar pattern was observed in the subgroup with diabetes, with a HR of 0.88 (95% CI 0.76 to 1.03) for primary composite end point (myocardial infarction, stroke or cardiovascular death) with no clear increase in bleeding risk [41].…”
Section: Secondary Preventionsupporting
confidence: 61%
“…Similarly, despite renal guidelines recommending statins in patients with CKD and known coronary artery disease, the use of statins was lower in patients with severe CKD, as was the use of P2Y12 inhibitors. Although most studies of anti‐platelet agents have not included patients with significant CKD, a recent post hoc analysis of the Platelet Inhibition and Patient Outcomes (PLATO) trial demonstrated an increased absolute risk reduction of major adverse cardiac events in patients with CKD and diabetes with the use of ticagrelor . However, this benefit needs to be balanced against the consistently higher incidence of bleeding in patients with acute MI treated with P2Y12 inhibitors in the setting of advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Reports published nearly two decades ago showed that mortality rates one year after successful PCI in DM patients with moderate and severe CKD were respectively, 5-and 12-times higher when compared to patients with normal renal function [21]. A subgroup analysis of the PLATO trial -a trial conducted over a decade ago [22], showed that patients with the combination of DM and CKD had a greater than 3-fold increase in the risk of mortality [6]. In the contemporary GLOBAL LEADERS trial, we found that despite the progressive improvements in stent design and secondary preventive pharmacotherapies, patients with both DM and CKD still had a 2.1-fold higher risk of mortality, 1.6-fold higher risk of repeat revascularization, and 1.6-fold higher risk of BARC 3 or 5 bleeding, compared with patients without these risk factors.…”
Section: Discussionmentioning
confidence: 99%